Oral squamous cell carcinoma presented only as a small swelling in attached gingiva: A case report - Tamrakar, Ritika; Pradhananga, Aagya; Gupta, Abhishek (Journal of Chitwan Medical College, 2025)
One of the most common malignancies of oral cavity, oral squamous cell carcinoma (OSCC) presents with ulcerative or proliferative lesions. Rarely, it presents as a small asymptomatic swelling, which can cause misdiagnosis and treatment delay. Histopathological confirmation is vital for accurate diagnosis due to a clinical similarity to benign inflammatory lesions or periodontal disease. We present a case of a 48-year-old male with a small, benign-looking indurated lesion of the attached gingiva. Histopathology confirmed squamous cell carcinoma. This case serves to emphasize the diagnostic difficulty of OSCC involving the gingiva, especially when it resembles periodontal disease or a benign gingival enlargement. Literature has shown that OSCC can have a misleading clinical presentation, resulting in inadequate management or undue delay in intervention. When assessing persistent, non-ulcerative gingival swellings, clinicians should maintain a high index of suspicion for malignancy, particularly for high-risk individuals with a history of smoking or tobacco use.